Hate the game : economic cheat codes for life, love, and work - Fairweather, Daryl (The University of Chicago Press, 2025)
"What economists know that we should know, translated for all of us. Should I buy or rent? Do I ask for a promotion? Should I tell people I'm pregnant? What salary do I deserve? Should I just quit this job? Common anxieties about life are often grounded in economics. In an increasingly win-lose society, these economic decisions-where to work, where to live, even how to live-have a way of feeling fixed and mistakes terminal. Daryl Fairweather is no stranger to these dynamics. As the first Black woman to receive an economics PhD from the famed University of Chicago, she saw firsthand how concepts of behavioral economics and game theory were deployed in the real world-and in her own life-to great effect. Hate the Game combines Fairweather's elite knowledge of these principles with her singular voice in describing how they can be harnessed. Her great talent, unique among economists, is her ability to articulate economic trends in a way that is not just informative, but also accounts for life's other anxieties. In Hate the Game, Fairweather fixes her expertise and service on navigating the earliest economic inflection points of adult life: whether to go to college and for how long; partnering, having kids, both, or neither; getting, keeping, and changing jobs; and where to live and how to pay for it. She speaks in actionable terms about what the economy means for individual people, especially those who have the sneaking suspicion they're losing out. Set against her own experiences and enriched with lessons from history, science, and pop culture, Fairweather instructs readers on how to use game theory and behavioral science to map out options and choose directions while offering readers a sense of control and agency in an economy where those things are increasingly rare"--